Meningkatkan Prestasi Belajar Matematika Melalui Metode Pembelajaran Kooperatif Model STAD (Student Teams Achievement Division) (Studi Kasus Siswa Kelas X RPL 5 SMK NEGERI 6 MALANG Tahun Ajaran 2012/2013) - Zuraidah (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2015)
One of factor that effected the result of mathematic teaching becomes low is the usage of inappropriate learningÂ method which used by teacher in a class. Because of that, the teachers are expected can develop a learningÂ method which involves the students directly into learning process so it can grow the ability of students toÂ develop, find, investigate, and show the idea. Learning method that involves the students directly is CooperativeÂ Learning Method.Â The aim of this research is: (1) to know the development of studentâ€™s achievement after the STAD cooperativeÂ learning method was applied towards student at grade X RPL in SMKN 6 Malang academic year 2012/2013. (2)Â to know the influence of study motivation from the students after the method is applied.Â This research is held in X RPL grade in SMKN 6 Malang academic year 2012/2013. The object of this researchÂ is student X RPL 5 grade which consist of 20 female students and 15 males students. The instrument inside thisÂ research is in a form of test. The Data about ability of students to understanding mathematic subject is takenÂ as long as the learning process and from the result of examination. Beside, the data about the development ofÂ learning quality is taken by seeing the change started from early learning process with next learning process.Â The data is collected and analyzed qualitatively and quantitatively (mixed methods).